Internal Control of Finance Information Systems on ERP Platform (Case Study : PT Petrokopindo Cipta Selaras) - Santoso, Safarianto Prio; Suryani, Erma (Institut Teknologi Sepuluh Nopember, 2020)
Businesses of any scale today cannot be separated from Information Systems and Technology, whether large or small scale requires a reliable information system to support appropriate, effective and efficient decision making for stakeholders. The information system that is currently trending in the business world is an Enterprise Resource Program (ERP) based on cloud computing (Cloud) which can help users run a business anywhere and anytime. In a report released by Delloite entitled: Hot Topics for IT Internal Audit In Financial Services reveals that the current hot issues are Cyber Security, Data Protection and Data Privacy, IT Governance and IT Risk. PT Petrokopindo is a company that has implemented cloud-based ERP. However, the potential for risks such as Cyber Security, Data Protection and Data Privacy from Cloud ERP can occur, which can disrupt the company's business operations. In this research, case studies will be carried out on companies that have implemented Cloud-ERP. The method used is the COBIT 5 Framework, which was chosen as the best and more complete guideline than other frameworks in the IT / IS management field (Sutikno, 2014). The expected result is to be able to identify security gaps and material weaknesses of the Cloud- ERP information system and then provide recommendations for improvements so that IS / IT becomes more reliable. It is hoped that this research can be useful for the development of IS / IT governance science, and as input for stakeholders on the Cloud-ERP platform in increasing the reliability of an IS / IT against the risk of information leakage and cyber attacks.